Public Interest in Mergers: South Africa. (June 2020) - Angumuthoo, Maryanne; Lotter, Derek; Wood, Shakti
In the pursuit of national policy objectives aimed at social and economic welfare for all South Africans, South African competition authorities have to use competition policy to achieve industrial policy goals through the implementation of public interest provisions in the Competition Act No. 89 of 1998. The recent amendments to the legislation further bolster these broader policy objectives. This issue of the Antitrust Bulletin examines the history, development, and impact of public interest considerations in merger proceedings through an analysis of seminal cases and key legislative reforms. Public interest considerations constitute a significant component to the merger review process and may involve interests represented by the competition authorities, government and employees, trade unions, and other affected third parties.